Impregnation of High-Magnetization FeCo Nanoparticles in Mesoporous Silicon: An Experimental Approach - Lepesant, Mathieu; Bardet, Benjamin; Lacroix, Lise-Marie; Fau, Pierre; Garnero, Cyril; Chaudret, Bruno; Soulantica, Katerina; Defforge, Thomas; Valente, Damien; Andreazza, Caroline; Billoué, Jérôme; Poveda, Patrick; et al. (Frontiers in Chemistry, 2018)
This paper deals with the synthesis of high-magnetization porous silicon-based nanocomposites. Using well-controlled organometallic synthesis of ferromagnetic FeCo nanoparticles, the impregnation of mesoporous silicon has been performed by immersion of porous silicon in a colloidal solution. The technique was optimized by controlling the temperature, the immersion duration and the solvent nature. The characterization of the nanocomposites showed a homogeneous filling of the pores and a high magnetization of 135 emu/cm3. Such composites present a great interest for many applications including data storage, medical instrumentations, catalysis or electronics.